Assessment of support systems and their impact on students’ skill acquisition in textiles education in selected Senior High Schools in Kumasi Metropolis - Adu-Poku, Achiaa (2021)
A thesis submitted to the Department of Educational Innovations in Science and Technology, College of Art and Built Environment, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the degree of Master of philosophy in art education.